Efektifitas Sistem Informasi Bisnis Menggunakan Model Delone dan Mclean Studi Kasus PT.Cahaya Anugrah Tama - Ismasari Nawangsih (Jurnal SIGMA, 2021)
Evaluation to an information system is necessary in order to know how far the system can achieve the objectives set and whether the system still needs to be maintained or not. This study aims to determine what factors are affecting the successful implementation of the model Sistem Informasi Bisnis (SiBis) and assess the effectiveness of information systems business model prevailing in company. Information System Success Model DeLone and McLean (2003) in theory and practice has been widely supported by several researchers to measure the success of information systems in organizations. This study aims to adopt the model of DeLone and McLean to test the 6 (six variables) that affect the success of the model of information systems such as the quality system (KS), the quality of information (KI), quality of service (KP), the use of (P), user satisfaction (KP), and net benefits (MB). There are 120 respondents participated in the study. Data were collected through surveys and analyzed by structural equation modeling (structured equation modeling) and the AMOS 7.0 software package. From this research result in getting that quality system (KS), the quality of information (KI), and the use of (P) does not affect the effectiveness of the business information system in PT.Cahaya Anugrah Tama. This is possible because the quality of information received users quickly and accurately because of the disruption of the quality system and the quality of service (KP) and user satisfaction (KPG) to study further on structuring variable model that will become a model that is adopted as the foundation in measuring the effectiveness of the company's business information system. Key words: Effectiveness, Success, Struktred Equation Modeling, AMOS.